A Systematic Review on the Improvement of Thermoregulating Properties of Cotton Fabrics with Nanocapsules of Phase Change Materials - Elnaz Rahimi; Azam Biabani; Maryam Ghaljahi; Farideh Golbabaei (بهداشت و ایمنی کار)
Introduction: Workers who work in warm situations need clothes with better thermal regulation. Nowadays, improving the thermal regulation properties of cotton fabric by treating it with phase change materials (PCMs) has been considered. The type of fabric plays an important role in providing thermal comfort. Cotton fabric is the most popular raw material in the textile industry due to its distinctive features. Therefore, this systematic review aims to investigate the effects of PCM nanoencapsulation in commonly used cotton fabrics, including morphology, thermal properties, thermal stability, tensile strength, abrasion resistance, leakage, water absorption, washing ability, and breathability of the fabric, related challenges, and future research trends. Material and Methods: This research was conducted with the papers obtained from the systematic search in Science Direct, Web of Sciences, Scopus, and PubMed databases. Keywords “nanoencapsulated phase change materials”, “nanoenhanced phase change materials”, “cotton”, “cotton fabric”, and “cotton textiles” were used. Results: Of the 1251 studies identified through search databases, 13 were selected according to the entry criteria. The results revealed that in all the studies, PCM nanocapsules were successfully synthesized and inserted into the cotton fabric, improving the fabric’s thermal properties. Most studies used in situ polymerization and mini-emulsion polymerization for nanoencapsulation. The pad-dry-cure method was also widely used for applying nanocapsules to cotton fabric. Conclusion: This systematic review showed that synthesized nanocapsules of phase change materials and applied them to cotton fabric can improve the thermoregulating properties of the fabric. It is suggested to expand the research to design thermoregulating clothes made from treated fabrics and investigate their cooling performance.